Some Weaker Forms of Continuous and Irresolute Mappings in Nano Ideal Topological Spaces - Parveen Banu Muhammed Jaffer; İnthumathi Velusamy; Abinprakash Ramalingum (Journal of New Results in Science)
The aim of this paper is to define and study certain newclasses of continuous and irresolute mappings namely nano α-I-continuous, nano semi I-continuous, nano pre I-continuous, nano α-I-irresolute, nano semi I-irresolute and nano pre I-irresolute mappings in nano ideal topological spaces and we discuss some of its properties. Finally, we obtain adecomposition of nanoα-I-continuous mapping.